Luminescent nanoparticles embedded in TiO2 microtube cavities for the activation of whispering-gallery-modes extending from the visible to the near infrared. Issue 18 (22nd April 2016) - Madani, Abbas; Ma, Libo; Miao, Shading; Jorgensen, Matthew R.; Schmidt, Oliver G.
Abstract : Luminescent nanoparticles (NPs) are deposited onto two dimensional (2D) pre-strained TiO2 nanomembranes by spin-coating. Abstract : Luminescent nanoparticles (NPs) are deposited onto two dimensional (2D) pre-strained TiO2 nanomembranes by spin-coating. After rolling up the 2D differentially strained TiO2 nanomembranes into 3D microtube structures, the NPs are embedded within the tube windings. The embedded NPs serve as a light source for optical whispering-gallery-mode resonances under laser excitation, and therefore allow the TiO2 microtube to work as an active microcavity operating in emission mode. The spectral range of resonant modes can be tuned from the visible to the near infrared by embedding the proper NPs in the TiO2 tube wall. Rolled-up TiO2 microcavities combined with luminescent NPs could offer interesting opportunities in a variety of research fields, such as bio- and nanophotonics, optoelectronics, and optofluidics.